Innovative Sustainability Initiatives: A Case Study of the Polytechnic School of Chimborazo in Ecuador - Miguel Tasambay Salazar; Rafael Córdova; Jenny García (Journal of Sustainability Perspectives, 2023)
Escuela Superior Politécnica de Chimborazo (ESPOCH), a higher education institution located in the central region of Ecuador, is one of the largest universities in the area, serving a student population of 19,349 and employing 1,091 teachers and 588 staff members. In 2022, the university was recognized for its sustainability efforts and ranked 386th in the UI GreenMetric World University Rankings. To further improve the university's sustainability indicators, the institution has prioritized initiatives related to energy and climate change, water management, and transportation. In order to reduce the university's carbon footprint, the first initiative involves implementing hybrid systems in campus buildings that utilize both photovoltaic energy and energy from the national electricity grid. Additionally, measures to increase energy efficiency and savings are being taken. For water management, the university is implementing a system to monitor water distribution for possible leaks, as well as devices to ensure efficient water use. A campaign promoting good environmental practices will also be launched. Lastly, to improve transportation, the university plans to implement an efficient transport management system within the campus, optimize the use of institutional vehicles, and encourage the use of environmentally friendly transportation options. ESPOCH is dedicated to placing sustainable initiatives at the forefront of its priorities while also decreasing its environmental impact. The institution utilizes both factfiles and experiences gained from participating in the UI World University Rankings as essential tools in guiding its efforts to improve the areas where it is weakest in terms of sustainability.